Comparative chemical screening and genetic analysis reveal tentoxin as a new virulence factor in Cochliobolus miyabeanus, the causal agent of brown spot disease on rice - De Bruyne, Lieselotte; Poucke, Christof Van; Di Mavungu, Diana Jose; Mohd Zainuddin, Nur Ain Izzati; Haecke, Lynn Van; Vleesschauwer, David De; Turgeon, B. Gillian; De Saeger, Sarah; Höfte, Monica (BSPP and John Wiley & Sons, 2016)
Brown spot disease, caused by Cochliobolus miyabeanus, is currently considered to be one of the most important yield reducers of rice (Oryza sativa L.). Despite its agricultural importance, little is known about the virulence mechanisms deployed by the fungus. Therefore, we set out to identify novel virulence factors with a role in disease development. This article reports, for the first time, the production of tentoxin by C. miyabeanus as a virulence factor during brown spot disease and the identification of the non-ribosomal protein synthetase (NRPS) CmNps3, responsible for tentoxin biosynthesis. We compared the chemical compounds produced by C. miyabeanus strains differing in virulence ability using ultra-high-performance liquid chromatography (UHPLC) coupled to high-resolution Orbitrap mass spectrometry (HRMS). The production of tentoxin by a highly virulent strain was revealed by principal component analysis of the detected ions and confirmed by UHPLC coupled to tandem-quadrupole mass spectrometry (MS/MS). The corresponding NRPS was identified by in silico genome analysis and confirmed by gene deletion. Infection tests with wild-type and Cmnps3 mutants showed that tentoxin acts as a virulence factor and is correlated with chlorosis development during the second phase of infection. Although rice has previously been classified as a tentoxin-insensitive plant species, our data demonstrate that tentoxin production by C. miyabeanus affects symptom development.